Morphological-based phylogeny and revision of Ciminius Metcalf and Bruner, 1936 (Hemiptera, Cicadellidae) - Luísa Alasmar; Alexandre Cruz Domahovski; Rodney Ramiro Cavichioli (Arthropod Systematics & Phylogeny)
In a morphological-based analysis using implied weighting for 23 taxa and 50 characters, we provided a phylogenetic study for Ciminius. The genus was recovered as monophyletic with a high support. We also provided a taxonomic revision, with description of three new species, increasing the diversity of Ciminius from seven to ten species: the Neotropical C. albolineatus, C. callosa, C. platensis, C. yana, C. autumnalis sp. nov., C. dissidens sp. nov., C. sesamum sp. nov., and the Nearctic C. hartii, C. sidanus, and C. taosus. A new monotypic genus, Arcanus gen. nov., recovered as sister to Ciminius is described. Tylozygus Fieber, the new genus, and Ciminius were recovered forming a clade here nominated as Articulate Stem Clade, due to its unique connective morphology amongst all Cicadellini. The immature stages of Ciminius sp. are described and a key to males, an occurrence map, and notes of parasitism and submacroptery are provided. We discussed the Ciminius relationships according to our analysis, the genus distribution, and the taxonomic problems about C. callosa.